Legal Review of Consumer Protection Against Ilegal Internet Network Providers - Nahdliyah, Hadziqotun; Isnaini, Enik; Anwar, Ahmad Brain (Jurnal Independent, 2024)
ABSTRACT The development of technology that almost all require Internet access. The Internet plays an important role in the globalization process. With business opportunities, there are some internet network providers who run their businesses without paying attention to applicable regulations so that in the future it can cause losses that have an impact on internet network consumers who have subscribed to the internet network business actors. The formulation of the problem in this study is: How is the legal protection of consumers as victims of illegal internet network providers. This research method uses a normative legal research method using a legislative approach and a conceptual approach. The legal materials in this study are primary legal materials and secondary legal materials. The results of this study can be concluded that before subscribing to an internet network, prospective customers must know the regulations that have been regulated in Law Number 8 of 1999 concerning Consumer Protection in order to minimize losses, in the law it has been regulated regarding consumer rights and obligations. Internet network consumers who are negatively impacted by illegal internet network providers have the right to protection such as access to information and assistance, the right to compensation, law enforcement, and prevention of violations that may occur in the future.